The role of emotions in discerning God’s will in missions: A comparison of the approaches of Ignatius of Loyola and J. Hudson Taylor - Lee, Jasmine (Missiology, 2025)
Discernment of God’s spiritual leading and an authentic basis for participation in missionary service is a vital foundation for resilience in missions. Additionally, emerging studies on emotions within Christianity demonstrate their being integral to human identity and behavior. The role of emotions in discernment for decision-making in missions has significant implications for motivation for missionary service. Analysis of the role of emotions in decision-making in the spiritualities of two leading historical mission leaders, Ignatius of Loyola and J. Hudson Taylor, reveal five key aspects of discernment. Passion for God and others, indifference to self, spiritual-emotional maturity, the ability to discern and confirm God’s voice, and knowing how to test external signs are all essential for correctly discerning the source of any revelation. Specifically developing these key aspects of discernment would be beneficial for missionary preparation and ongoing spiritual formation.